2017
DOI: 10.3390/rs9111183
|View full text |Cite
|
Sign up to set email alerts
|

Identification of C-Band Radio Frequency Interferences from Sentinel-1 Data

Abstract: Abstract:We propose the use of Sentinel-1 Synthetic Aperture Radar (SAR) to provide a continuous and global monitoring of Radio Frequency Interferences (RFI) in C-band. We take advantage of the first 8-10 echo measures at the beginning of each burst, a 50-70 MHz wide bandwidth and a ground beam coverage of~25 km (azimuth) by 70 km (range). Such observations can be repeated with a frequency better than three days, by considering two satellites and both ascending and descending passes. These measures can be used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 9 publications
0
15
0
Order By: Relevance
“…Figure 6a illustrates possible terrestrial radio emitters. In recent years, many terrestrial RFI cases have been observed in airborne SAR systems such as AIRSAR [18,19], E-SAR [20], UAVSAR [5], and space-borne SAR systems like PALSAR [21,22] and Sentinel-1 [23][24][25]. Figure 6b illustrates the interfering mechanism between the terrestrial RFI and the SAR system.…”
Section: Terrestrial Rfi Sourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 6a illustrates possible terrestrial radio emitters. In recent years, many terrestrial RFI cases have been observed in airborne SAR systems such as AIRSAR [18,19], E-SAR [20], UAVSAR [5], and space-borne SAR systems like PALSAR [21,22] and Sentinel-1 [23][24][25]. Figure 6b illustrates the interfering mechanism between the terrestrial RFI and the SAR system.…”
Section: Terrestrial Rfi Sourcesmentioning
confidence: 99%
“…Reference source not found. ], and space-borne SAR systems like PALSAR [20,21] and Sentinel-1 [22][23][24]. Figure 6b illustrates the interfering mechanism between the terrestrial RFI and the SAR system.…”
Section: Terrestrial Rfi Sourcesmentioning
confidence: 99%
“…The balance between ground and LEO RFI is different in the two frequencies: the C-band systems are more subject to on-ground RFI, since the band is open to ground services like weather radar [8,9], whereby X band is primarily allocated to ESS-Active (Exploration Satellite Service), that should, in principle, exclude on-ground RFI. However, the number of present and future X band SARs, like the forthcoming constellations of light SARs: ICEYE, Capella Space or UmbraLab, is so large to motivate the in-depth analysis performed in the paper, and the need for a performance model capable of adapting to present and future scenarios.…”
Section: Introductionmentioning
confidence: 99%
“…The process of estimating soil moisture from C-band SAR data is complicated by scattering from vegetation (Lang and Sidhu, 1983), scattering due to soil surface roughness (Álvarez-Mozos et al, 2009;Martinez-Agirre et al, 2017), temperature dependence (Rodionova, 2017b), scattering from man-made objects (Tadono et al, 2000) and sources of radio frequency interference (RFI) (Monti-Guarnieri et al, 2017).…”
Section: Factors Affecting C-band Sar Soil Moisture Estimationmentioning
confidence: 99%